Hormone Receptors and HER2 Status of Patients with Breast Cancer in a Tertiary Center of Nepal: A Descriptive Cross-Sectional Study - Paudel, Bishal; Panthi, Bishal; Shrestha, Rakshya; Gyawali, Siddinath; Kharel, Sanjeev (Journal of Institute of Medicine Nepal, 2023)
Introduction The second most prevalent cancer among women in Nepal is breast cancer. The assessment of human epidermal growth factor receptor-2 (HER2), progesterone receptor (PR), and estrogen receptor (ER) status in patients with breast cancer is currently regarded as standard practice because of its prognostic and predictive value. This study aims to find the incidence of Hormone receptor and HER2 status in patients with breast cancer. Methods This is a descriptive observational cross-sectional study that assessed the immunohistochemistry markers of different histological types of breast cancer patients who visited a tertiary center in Nepal. Retrospective data from August 1, 2022, to July 30, 2023, were gathered from computer records of all the patients diagnosed with breast cancer who visited the Tribhuvan University Teaching Hospital (TUTH). SPSS version 26.0 was used for statistical analysis. Results A total of 102 patients with breast cancer were included. The mean age of the patients was 50.51±12.08 years. Only one patient was male. The analysis showed that 62 (60.78%) of total patients had ER/PR positive breast cancer and 40 (39.2%) were HER2 positive with a higher number among Janajati and the age group 41-60 years. Similarly, the incidence of triple-negative breast cancer was 21 (20.59%) of all patients. Conclusion The majority of breast cancer patients in our study were ER/PR positive, followed by HER2-positive and triple-negative cases. A higher prevalence was observed among the Janajati ethnic group and those aged 41-60 years.